THE DIAGNOSIS OF LIVER ALLOGRAFT ACUTE REJECTION IN LIVER BIOPSIES - L. V. Shkalova; N. P. Mogeiko; I. M. Iljinsky; Y. G. Moysyuk; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов)
We performed histological examination of 80 liver allograft biopsies, the diagnosis of acute rejection was proved in 34 cases. Histological changes in liver biopsies in different grades of acute rejection were estimated according to Banff classification 1995, 1997 and were compared with current literature data. The article deals with the question of morphological value of grading acute rejection on early and late, also we analyze changes in treat- ment tactics after morphological verification of liver allograft acute rejection.